Paradigmatic and Syntagmatic Relations in the Qur’an: A Structural-Semiotic Reading of Qur’anic Human Creation Verses - Ubaidillah Ubaidillah; Bambang Hariyanto; Amin Nasir; Samsul Anam; Ghazali Zainuddin; Siti Rosilawati Ramlan (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
This article examines the phases of human creation in the Qur'an through Ferdinand de Saussure's structural linguistic framework, with particular attention to paradigmatic (lexical selection) and syntagmatic (sequential arrangement) relations operative in key verses: QS al-Mu'minūn [23]:12–14, al-Ḥajj [22]:5, as-Sajdah [32]:7–9, and al-Insān [76]:2. Employing a qualitative descriptive method with content analysis, the study draws on primary data comprising Qur'anic texts and secondary data from classical and contemporary exegetical works. The analysis demonstrates that lexical variations, including ṭīn (clay), turāb (soil), sulālah (essence of earth), and nuṭfah (seminal fluid), constitute a system of paradigmatic oppositions that encodes a graduated ontological progression from material origin to spiritual endowment. Syntagmatic relations, realized through conjunctions such as ṡumma and fa, organize these stages into a coherent narrative sequence that moves from physical formation to the bestowal of cognitive and spiritual faculties. Accordingly, the language of the Qur'an functions not merely to describe biological processes but to construct a conceptual framework through which human identity, origin, and existential purpose are discursively represented. This study concludes that the Qur'anic linguistic structure constitutes a theologically organized semiotic system in which lexical selection and syntagmatic patterning jointly produce a layered discourse of human existence — one that integrates the material, biological, spiritual, and cognitive dimensions of personhood within a unified sign system.